MAPK9 is Correlated with a Poor Prognosis and Tumor Progression in Glioma - Xinyu Yang; Qingge Jia; Xuantong Liu; Weidong Wu; Yuwei Han; Zheng Zou; Mingyang Li; Di Fan; Junyang Song; Ligang Chen (Frontiers in Bioscience-Landmark, 2023)
Background: Glioma has a high incidence in young and middle-aged adults and a poor prognosis. Because of late diagnosis and uncontrollable recurrence of the primary tumor after failure of existing treatments, glioma patients tend to have a poor prognosis. Recent advances in research have revealed that gliomas exhibit unique genetic features. Mitogen-activated protein kinase 9 (MAPK9) is significantly upregulated in mesenchymal glioma spheres and may be a new target for glioma diagnosis. This study aimed to investigate the potential diagnostic significance and predictive value of MAPK9 in glioma. Methods: Paraffin-embedded tumor tissues and paracancerous tissues were collected from 150 glioma patients seen at the General Hospital of Northern Theater Command. Immunohistochemistry and western blot assays were used to detect the expression levels of MAPK9. Prognosis and survival analyses were performed using SPSS 26 software for univariate/multivariate analysis and log-rank analysis. Cellular models were used to assess the effect of MAPK9 overexpression and knockdown in vitro. Results: MAPK9 expression was higher in glioma tissues than in paraneoplastic tissues. Prognostic and survival analyses revealed that the MAPK9 expression level is an independent prognostic factor in glioma patients. In addition, overexpression of MAPK9 significantly promoted the proliferation and migration of primary glioma cells, possibly via the Wnt/β-catenin-regulated EMT pathway. Conclusions: MAPK9 is an independent prognostic factor in glioma and is involved in tumor progression.